Fabrication of artificial defects in NDT Reference Block using 3D printing - Seng, Guo Yuan (2018)
A reference block with irregular reflectors and two planar reflectors was designed and printed using an additive manufacturing process called selective laser melting. Variables such as shape of reflector wall, depth and orientation of reflector were made. The purpose was to evaluate how these variables affect echo signal from non-destructive testing such as ultrasonic scan. The combination of variation in shape of reflector wall and reflector depth in reflector 2 has the largest effect on the echo signal and location. Echo signal amplitude was reduced, and location of reflector measured deviated from actual location. Open-hole high frequency eddy current test was conducted and successfully identify reflector relative locations and allow a comparison in length. Dimensional measurements of the printed features were made through evaluations of cross-sectional images from CT scans. Maximum standard deviation of +/- 0.15mm was taken as tolerance of the fabrication process. The tolerance did not meet the requirement stated in AMS standard. Acoustic attenuation measured on two specimens was not consistent, the average value can only be use as a guideline to characterise the printed material. Acoustic velocity and electrical conductivity measured were more consistent and could be use to identify the material. Acoustic properties such as impedance and velocity were to be comparable to some aluminium alloy. This could suggest that the printed material of this experiment could be used as an equivalent material to fabricate reference standard of these aluminium alloy.